Persistence of Streptococcus mutans in Stationary-Phase Batch Cultures and Biofilms - Renye, John A. (American Society for Microbiology, 2004)
Streptococcus mutans is a member of oral plaque biofilms and is considered the major etiological agent of dental caries. We have characterized the survival of S. mutans strain UA159 in both batch cultures and biofilms. Bacteria grown in batch cultures in a chemically defined medium, FMC, containing an excess of glucose or sucrose caused the pH to decrease to 4.0 at the entry into stationary phase, and they survived for about 3 days. Survival was extended up to 11 days when the medium contained a limiting concentration of glucose or sucrose that was depleted by the time the bacteria reached stationary phase. Sugar-limited cultures maintained a pH of 7.0 throughout stationary phase. Their survival was shortened to 3 days by the addition of exogenous lactic acid at the entry into stationary phase. Sugar starvation did not lead to comparable survival in biofilms. Although the pH remained at 7.0, bacteria could no longer be cultured from biofilms 4 days after the imposition of glucose or sucrose starvation; BacLight staining results did not agree with survival results based on culturability. In both batch cultures and biofilms, survival could be extended by the addition of 0.5% mucin to the medium. Batch survival increased to an average of 26 (±8) days, and an average of 2.7 × 10(5) CFU per chamber were still present in biofilms that were starved of sucrose for 12 days.